General Overview of Previous Advances on Polyhydroxyalkanoates (PHA) Synthesis by Microorganism Utilizing Different Waste Carbon Sources - Afghan, Inzer Gul; Hashmi, Ajmal; Ali, Abdul (Journal for Research in Applied Sciences and Biotechnology, 2022)
This review paper denotes recent advances of Polyhydroxyalkanoates (PHA), derived from bacterial fermentation of sugars or lipids. Polyhydroxyalkanoates (PHA) are biodegradable polyesters, (PHA) has many hydroxyl groups depend on carbon sources. This study gives overview of recent research dealing with PHA synthesis, utilizing various carbon sources producing biodegradable polymers, degrading of PHA by microorganism to water and carbon dioxide found in soil, sewage and water, therefore, PHA Production increased under salty medium such as sodium chloride, bioplastic was characterized by FTIR, DSC, TGA, and NMR. recent studies on contaminant treatment, tissue engineering and fermentation strategies can give comprehension for researchers to design production of bioplastics from waste carbon sources. Also cost effective PHA synthesis, this review explores beneficial information about the limit affiliate with the tolerable PHA synthesis utilizing different waste carbon sources. various great advances have been generated: different wastes as raw material, various extraction pathways, and meet design of bioplastic. This review paper resumed the scientific and technological improvement of PHA through their discovery in 1888 up to their recent applications and most current commercial utilization.